Assessing reduction in concrete shear strength contribution - Arslan, Guray; Alacali, Sema; Sagiroglu, Ali (ICE PUBLISHING, 2016)
Design codes use a strength reduction factor that is less than unity. This factor reflects the degree of uncertainty associated with the probability of under-strength members and inaccuracies in the design equations, the importance of the member in the entire structure and the behaviour of a member at ultimate load. A failure probability based on a second moment probabilistic analysis procedure is used in this study to compute the strength reduction factor in predicting the contribution of concrete to shear strength of reinforced-concrete beams according to the American Concrete Institute code ACI 318. For different coefficients of variation of concrete and failure probabilities, the shear strength reduction factor is investigated using experimental studies available in the literature. It is assumed that the random variables are statistically independent, and the correlation effects are not taken into account. It is found that a strength reduction factor of 0.75 for shear is valid in design according to ACI 318 for a coefficient of variation of concrete compressive strength of 0.18 and a failure probability of 10(-5).
Keywords: beams & girders; failures; risk & probability analysis; DIAGONAL CRACK-PROPAGATION; RELIABILITY-BASED DESIGN; NONLINEAR-ANALYSIS; BEAMS; Construction & Building Technology; Engineering